Determinan Pelarangan PraktikShort Selling dalam Lingkup Pasar Modal Syariah dan Realitasnya di Indonesia - Wiwiek R. Adawiyah; Najmudin Najmudin (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2011)
Capital market is an activity related to public offering and trading of securities, public companies relating to the issuance of securities, institutions and professionals associated with the effects. One of the most popular financial instruments and commonly used in conventional capital market, including in Indonesia Stock Exchange (Bursa Efek Indonesia) is short-selling. In regulation of Bapepam-LK No. V.D.6, short-selling is the sale of securities in which the securities are not owned by the seller when the transaction is executed. In general, this transaction clearly violated syariah guidance, as embodied in the Fatwa of DSN-MUI No. 20 Year 2001 and No. 40 year 2003, because of short-selling synchronized with the bay' ma'dum based on the hadith "You may not sell anything which are not your belongings". Therefore, this paper aims at studying the issues surrounding the interpretation and the reality of short-selling instruments. Three main results obtained were permissibility of shares as the object of the loan contract, the issue of bay 'ma'dum can be interpreted as a collateral of delivery which can be controlled by the rules of Bapepam-LK, and thirdly, the economic benefit from the imposition of a fee in the formof the loan contract is concluded as a forbidden usury.